CAN AUDIT QUALITY AND FINANCIAL PERFORMANCE AFFECT PROFIT MANAGEMENT IN SHARIA COMMERCIAL BANKS IN INDONESIA? - RUDI ARYANTO; PUTRI ANDREANI; FAKHRINA FAKHRINA (Prodi Manaj. Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam – UIN Imam Bonjol Padang, 2023)
This study aims to determine the effect of Audit Quality and Financial Performance on Earnings Management in Islamic Commercial Banks. The population in this study is 14 Islamic Commercial Banks in Indonesia in 2018-2020. The sample in this study totaled 30 samples from 10 Islamic Commercial Banks with an observation period of 3 years, using a purposive sampling method. This study uses multiple regression analysis techniques to test the hypothesis through the SPSS 25 program. The test results partially show that the variables of Audit Quality and Financial Performance have no effect on Earnings Management.